Management Lessons from an Academic Presidential Search - Ware, Fred A. (Southeastern Case Research Journal, 2003)
This case, focusing on the activities of an academic institution’s presidential search committee, illustrates multiple decision points in every classical management function as encountered under intense time pressure and within legally-impacted confidentiality constraints. Written from an actual event, it is appropriate for courses in organizational behavior, human resource management, and educational leadership; it would be useful at undergraduate, graduate, or executive levels. The student encounters numerous and diverse examples of conflicts and procedural interruptions, some which develop gradually and others which are unanticipated and sudden. The case is seen from the perspective of the ad hoc committee chairperson, virtually blindsided by new responsibilities, then challenged to balance his use of time and energy while handling normal job duties. Individual scenarios can be used as incidents to illustrate specific management concepts.